Radiation hybrid maps of candidate trypanotolerance regions in cattle - Nilsson, P.H.; Kang'a, S.; Rottengatter, K.; Suedbeck, U.; Iraqui, F.; Mwakaya, J.; Mwangi, D.; Womack, J.E.; Goldammer, T.; Schwerin, M.; Bradley, D.; Agaba, Morris; et al. (1999)
A preliminary search for QTLs in a cattle F2 resource populations segregating for trypanotolerance has revealed three large candidate chromosomal regions (Bta02, Bta05, Bta07). In order to narrow down the position of the trypanotolerant QTLs, we are building comparative chromosomal maps between cattle, human and mice. Using a cattle radiation hybrid panel, first framework maps are constructed with type II markers (microsatellites). Then, type I markers (genes) are positioned within these maps. Their relative chromosomal positions, compared to their positions in human and mice, allow us to define conserved syntenic regions between the three species. The large number of genes being identified in human and mice may assist selection of candidate genes.